Pengaruh Pendidikan Kesehatan Melalui Media Sosial Terhadap Pengetahuan Ibu Nifas Tentang Teknik Menyusui pada Masa Pandemi COVID 19 di Wilayah Kerja Puskesmas Puncu Kabupaten Kediri - Wigati, Putri Wahyu; Miftakhul Mualimah (Universitas Nusantara PGRI Kediri, 2021)
Breastfeeding with improper technique can cause sore and swollen nipples. Improper breastfeeding technique can also interfere with the production and transfer of breast milk to the baby. From a preliminary study of 10 postpartum mothers, 6 (60%) in postpartum mothers, namely the lack of understanding of the correct breastfeeding technique, causing the baby to spit up, sore nipples and sore nipples, while 4 (40%) in postpartum mothers had a good understanding so they did not experience nipples. milk blisters and breastfeed properly so that the baby is comfortable when breastfed by the mother. The purpose of this study was to determine the effect of health education through social media on knowledge about breastfeeding techniques for postpartum mothers. This inferential study with a pre-experimental design, the population is postpartum mothers with a sample of 20 respondents using purposive sampling technique. Data collection using google form, Wilcoxon analysis test. Based on the results of the research, most of the 14 (70%) knowledge before being given health education were lacking while after giving health education through social media almost all 16 (80%) had good knowledge. From the results of the data test using the analysis, it was found that a p-value of 0.000, at a significant level of (alpha) 0.05 so that Ho was rejected and H1 was accepted, which means that there is an influence of knowledge of health education on breastfeeding techniques through video media. Health education through social media media can increase knowledge of breastfeeding techniques so that there will be no more difficulties in the breastfeeding process. Based on the results of the research, it is hoped that the research area will increase counseling and counseling about good and correct breastfeeding techniques through social media.